Extending urban stories through artistic research: the case of Jetty Street. Issue 4 (4th July 2019) - Filep, Crystal Victoria
ABSTRACT: This paper focuses on extending the narrative potential of urban design and public art through artistic research. It is a creative extension of a project from the author's professional urban design practice. Supported by photographs and contextual descriptions, the central focus is an original watercolour that explores the project's reclamation and generation of site-specific stories beyond conventional limits. Fragments of place embed themselves in the imaginations of those who create – and, later, experience – that place, influencing the continuous two-way people-place exchange. Urban design efforts could benefit from further research on possible impacts generated from such imaginative reflections within this exchange.